Neoadjuvant Chemoradiation in Squamous Cell Carcinoma of the Maxillary Sinus: A 26-Year Experience. (29th September 2012) - Kreppel, Matthias; Danscheid, Sarah; Scheer, Martin; Lüers, Jan Christoffer; Eich, Hans Theodor; Zöller, Joachim E.; Guntinas-Lichius, Orlando; Beutner, Dirk
Abstract : Background . The aim of our study was to evaluate the effects of neoadjuvant platinum-based radiochemotherapy (RCT) in patients with maxillary sinus squamous cell carcinoma and to compare the results with other multimodality treatment concepts for advanced-stage maxillary sinus carcinoma in the literature. Methods . In total, 53 patients with squamous cell carcinoma of the maxillary sinus were reviewed retrospectively. All patients received a neoadjuvant RCT containing either cisplatin or carboplatin followed by radical surgery. Overall survival and locoregional control were plotted by Kaplan-Meier analysis. Prognostic factors were identified through univariate and multivariate analysis. Results . Five-year overall survival for all patients was 35%. Eleven patients achieved a complete response after radiochemotherapy. The complete response rate was significantly higher for patients treated with cisplatin (P = 0.028 ); however the 5-year overall survival rates did not differ significantly (P = 0.673 ) for patients treated with cisplatin (37%) and carboplatin (32%). Orbital invasion (P = 0.005 ) and complete response to radiochemotherapy (P = 0.021 ) had a significant impact on overall survival in univariate analysis. Conclusions . Neoadjuvant radiochemotherapy followed by radical surgery is an effective treatment for patients with advanced maxillary sinus squamous cell carcinoma. In terms of treatment response cisplatin seems to be more effective than carboplatin.